LOBBYIST BURNS UP ANTI - SMOKING ZEALOTS - MORGAN,TJ (Tufts Archival Research Center, 2007)
Providence Journal article on Tobacco Institute lobbyist Raymond Oliviero. Discusses his efforts to defeat smoking bans in Massachusetts. Outlines argument between Oliviero and the American Lung Association, focusing on the argument over what constitutes valid research.